Control of nitrogenase recovery from oxygen inactivation by ammonia in the cyanobacterium Anabaena sp. strain CA (ATCC 33047). - Smith, R L (1990)
The control of nitrogenase recovery from inactivation by oxygen was studied in Anabaena sp. strain CA (ATCC 33047). Nitrogenase activity (acetylene reduction) in cultures grown in 1% CO2 in air was inhibited by exposure to 1% CO2-99% O2 and allowed to recover in the presence of high oxygen tensions. Cultures exposed to hyperbaric levels of oxygen in the presence of 10 mM NH4NO3 were incapable of regaining nitrogenase activity, whereas control cultures returned to 65 to 80% of their original activity within about 3 h after exposure to high oxygen tension. In contrast to the regulation of heterocyst differentiation and nitrogenase synthesis, recovery from oxygen inactivation in this organism was shown to be under the control of NH4+ rather than NO3-.